Evaluation of pro‐inflammatory markers plasma C‐reactive protein and urinary prostaglandin‐E2 metabolite in colorectal adenoma risk. Issue 8 (31st August 2015) - Davenport, James R.; Cai, Qiuyin; Ness, Reid M.; Milne, Ginger; Zhao, Zhiguo; Smalley, Walter E.; Zheng, Wei; Shrubsole, Martha J.
Abstract : C‐reactive protein (CRP) is a pro‐inflammatory protein with potential as a biomarker in predicting colon cancer risk. However, little is known regarding its association with risk of colorectal adenomas, particularly by subtypes. We conducted a colonoscopy‐based matched case‐control study to assess whether elevated plasma CRP levels may be associated with colorectal adenoma risk and further whether this association may be modified by urinary prostaglandin E2 metabolite (PGE‐M), a biomarker of systemic prostaglandin E2 production. Included in the study were 226 cases with a single small tubular adenoma, 198 cases with multiple small tubular adenomas, 283 cases with at least one advanced adenoma, and 395 polyp‐free controls. No apparent association between CRP level and risk of single small tubular adenomas was found ( p trend = 0.59). A dose‐response relationship with CRP level was observed for risk of either multiple small tubular adenomas (OR = 2.01, 95%CI = 1.10–3.68 for the highest versus lowest tertile comparison; p trend = 0.03) or advanced adenomas (OR = 1.81, 95%CI = 1.10–2.96 for the highest versus lowest tertile comparison; p trend = 0.02). In a joint analysis of CRP level and PGE‐M, risk of multiple or advanced adenoma was greatest among those with highest levels of both CRP and PGE‐M in comparison to those with low CRP and low PGE‐M (OR = 3.72, 95%CI = 1.49–9.72). Our results suggest that elevated CRP, particularly in the context of concurrent elevated PGE‐M, may be a biomarker of multiple or advanced adenoma risk in a screening age population. © 2015 Wiley Periodicals, Inc.